Antibiotic Prophylaxis in Plastic Surgery Correlation Between Practice and Evidence. Issue 2 (May 2021) - Mankowski, Peter; Cherukupalli, Abhiram; Slater, Karen; Carr, Nick
Background: The use of appropriate preoperative antibiotic prophylaxis decreases the risk of surgical site infections (SSI); however, the breadth of plastic surgery procedures makes it challenging to ensure appropriate use for each unique procedure type. Currently, plastic surgeons lack a cohesive and comprehensive set of evidence-based guidelines (EBG) for surgical prophylaxis. We sought to profile the perioperative antibiotic prescribing patterns for plastic surgeons in British Columbia to investigate if they are congruent with published recommendations. In doing so, we aim to determine risk factors for antibiotic overprescribing in the context of surgical prophylaxis. Methods: A literature review identifying EBG for antibiotic prophylaxis use during common plastic surgery procedures was performed. Concurrently, a provincial survey of plastic surgery residents, fellows, academic and community plastic surgeons was used to identify their antibiotic prophylaxis prescribing practices. These findings were then compared to recommendations identified from our review. The compliance of the provincial plastic surgery community with current EBG was determined for 38 surgical scenarios to identify which clinical factors and procedure types were associated with unsupported antibiotic use. Results: Within the literature, 31 of the 38 categories of surveyed plastic surgery operations have EBG for use of prophylactic antibiotics. When surgical procedures have EBG, 19.5% of plastic surgery trainees and 21.9% of practicing plastic surgeons followed recommended prophylaxis use. Average adherence to EBG was 59.1% for hand procedures, 24.1% for breast procedures, and 23.9% for craniofacial procedures. Breast reconstruction procedures and contaminated craniofacial procedures were associated with a significant reduction in adherence to EBG resulting in excessive antibiotic use. Conclusion: Even when evidence-based recommendations for antibiotic prophylaxis exist, plastic surgeons demonstrate variable compliance based on their reported prescribing practices. Surgical procedures with low EBG compliance may reflect risk avoidant behaviors in practicing surgeons and highlight the importance of improving education on the benefits of antibiotic prophylaxis in these clinical situations.